Uma experiência de incentivo à leitura com alunos do 9º ano de uma escola do campo na realidade da Transamazônica - OLIVEIRA, Jorge Antônio de Assis (2021)
The domain of language, in the different aspects of the written and spoken word, of reading and orality, is crucial for our life. Starting from these assumptions, the project was born at Escola do Campo Liberdade II, with the title "And the verb was made phrases, words and poetry and we learned our history", elaborated in Community Time, as an academic of the Course of Field Education Languages and Codes and professor of Portuguese Language of said school of the community Padre Josimo, KM 130 Norte, municipality of Medicilândia - PA. Observing the results of this project, there was interest in developing such a topic as a Course Completion Work, in addition to noting the difficulties of the School of the Field in terms of availability of didactic material and historical delay in the scope of reading practice. Aiming in general to work diversified methodologies in the process of teaching Portuguese Language in the field reality, and seeking, through Literature, to awaken the habit of reading, producing, interpreting and improving the orality of learners;. Finally, it was possible to verify that, through the developed project, the students were easier to communicate through the themes developed, and a noticeable improvement in reading, writing, oratory and socialization.